Vaccine hesitancy among parents of children in their first two years of life - Magyar, Ruth; Voitl, Peter K.; Voitl, Julian J. M.; Diesner-Treiber, Susanne C. (Frontiers in Public Health, 2024)
Background Vaccine hesitancy is considered a primary cause of outbreaks of vaccine-preventable infectious diseases. The Austrian vaccination plan includes 24 vaccinations in the first 2 years of life, 12 for free and 12 subject to a fee. Since preterm babies are more susceptible to severe infections, immunization is a vital protection strategy. This study examines the routine immunization schedule recommended for children in Austria, the number of timely vaccinations, and the number of delayed and rejected vaccinations. Possible reasons for vaccination delays and rejection and potential influencing factors (preterm birth, COVID-19 pandemic, information sources) are also analyzed. Methods We included children aged 2 to 5 years who presented to Vienna's largest pediatric center with an Austrian mother-child pass and spent the first 2 years of their lives in Austria. Data was collected using questionnaires about the vaccination status, parents' reasons for any rejections or delays in the recommended vaccination regimen, the impact of the COVID-19 pandemic on individuals' vaccination behavior, and child-specific influencing factors such as preterm birth and socioeconomic factors. Results 90% of the 150 study subjects follow the recommendations on routine vaccinations, while 40–62% accept vaccinations subject to a fee. Preterm infants received less fee-based (53%) as well as gratuitous (88%) vaccinations. While free vaccinations tend to be delayed, more fee based vaccinations are rejected. With free vaccinations, delays and refusals occur due to illness or missed appointments. In the case of fee- required vaccinations, however, fears of side effects are also one of the main reasons. Due to the COVID-19 pandemic, about a quarter of parents have become more skeptical about vaccines. However, the vaccination rate of premature babies is usually just below that of full-term babies. Physicians remain the most trustworthy source of information about vaccinations. Conclusion Free vaccinations are more accepted by parents than fee based vaccinations. Preterm babies, which are a high risk group for vaccination preventable diseases, show a lower or delayed vaccination rate, which must be prevented through intensive doctor education. In addition, vaccination hesitancy changed during the COVID-19 pandemic, which needs to be addressed during the medical consultation.